Water use and water use efficiency of mustard Waruna’ on Saline-Sodic soil in Central Uttar Pradesh - Khokhar, R.P.S.; bhan, Suraj; Agrawal, S.K. (Journal of Soil and Water Conservation, 2022)
Water use and water use efficiency of mustard ’Varuna’ were studied on newly reclaimed saline-sodic soil of Gangetic Alluvium in relation to frequency of irrigaion and levels of nitrogen for 3 consecutive years from 1978-79 to 1980-81 at the University Research Farm, Dalipnagar, Kanpur. The results revealed maximum water use fir mustard (31.99 en:) when supplied with 6 irrigations. Likewise the crop fertilized with 160 kg N/ha gave maximum water use (30.61 cm) which was 3.22 cm more than the unfertilized crop. However, the water use efficiency was highest (3.62 kg/ha/pint) in seed production and 17.72 kg/ha/mm in dry ’natter production when the crop was provided 5 irriga- tions at 20,30,50, 75 and 100 days of crop age. Nitrogen application tremen- dously increased the water use efficiency both in seed and total thy matter production, the maximum being with 120 kg in seed production and 160 kg A7lia in total dry matter production. As regards the water productivity; it was maximum with 3 irrigations but 5 irrigations at 20, 30, 50, 75, and 100 days after solving also gave good water productivity. Likewise a dose of 120 kg N/ha was found to give maximum water productivity. Proper water management merits great attention in successful crop production on salt affected soils and more so on sodic-soils Both excess and &rent supply of water affects the crop growth on such soils. Nutritional imbalance and reduced availability of many plant nutrients, is another important problem encountered on such soils. Since there is dearth of information on proper soil moisture and fertility balance on salt affected soils to have a successful harvest of mustard in initial years of reclamation, the present study was undertaken at Daliptzagar, Kanpur.